Estudo teórico e experimental da levitação acústica de campo próximo - Zuffi, Geisa Arruda (2022)
Near-field Acoustic levitation occours when a squeezed film is created between a driven surface and the object to be either transported or levitated. The driven surface is then responsible for the pressurization of the gas (usually the air), which occurs due to its large amplitude and high frequency oscillations (ultrasonic frequency, greater than 20 kHz), normally achieved through the use of ultrasonic transducers (more commonly a Langevin transducer) operating in resonance condition. The increase in the pressure of this gas will depend on its viscosity and compressibility. Besides, the average of the resulting pressure field generated (in the time domain) should be greater than the pressure of the environment in which the levitation system is inserted. Thus, near-field acoustic levitation is part of the search for alternatives that allow for the transport and storage of objects and substances without contact between surfaces, so that linear or rotational high-speed movements in machines may occur without the use of conventional lubricants. However, this technique has limitations with respect to applications where a high load capacity is required. Therefore, this work aims to analyze the behavior of the near-field acoustic levitation technique under different conditions in order to determine which agents exert some influence on its carrying capacity. For this aim, the numerical model of a near-field acoustic levitation system with the object to be levitated fixed and free is presented. Then, the interval uncertainty and sensitivity analyses technique is applied in order to evaluate the effects of uncertainties on both the operational (drive frequency, drive surface size, vibration amplitude) and environmental (initial pressure and ambient fluid viscosity) parameters regarding the near-field acoustic levitation performance. In this way, it was possible to verify that the load capacity of the levitation system with the upper disk fixed, is more sensitive to the uncertainties applied in the environmental conditions and in the operational frequency. While the levitation system with the upper disc free has its performance more influenced by the operational parameters (amplitude of vibration and size of the actuation surface). Finally, a comparative experimental study is carried out between near-field acoustic levitation systems with drive surfaces with and without grooves and comparative numerical analyzes between systems without textures (smooth drive surface), with grooves of different sizes and with steps in different positions. different. In general, the smooth drive surface presented the best performance among those evaluated, followed by the stepped surface.